Navigating underrepresentation and gendered barriers to women's political power: Narratives and experiences of women parliamentarians in Turkey - Ehrhart, Anna (Frontiers in Political Science, 2023)
As women increasingly participate in political decision-making around the world, the research emphasizes the need to further understand how informal barriers shape women's political participation. At the same time, the persistent stability of hybrid political regimes calls for additional inquiry into the impact of hybrid regimes on gender politics and its actors. Based on the case of Turkey, a hybrid regime, this study explores how women MPs navigate gendered, informal obstacles in parliament and to what extent their navigation strategies reflect the broader implications posed by the hybrid regime context. This exploratory study draws on qualitative, in-depth semi-structured interviews with eight women MPs in the Turkish parliament from government and opposition parties. The findings illustrate that navigating the informal barriers women MPs experience in the Turkish parliament happens both individually and in collective ways. Individually, women MPs choose to navigate the informal barriers of gender norms by either assimilating or contrasting the masculine way of doing politics. Collective navigation strategies of women MPs in the Turkish parliament illustrate their approaches to representing women's interests, seeking women's solidarity across the parliament, and linkages with civil society to empower women, which also reflect the different positionings of government and opposition within the Turkish hybrid regime dynamics. The findings reveal the need to further research the complex, dynamic interplay of how informal practices and hybrid regime tactics target gender politics and its actors, while also giving more attention to women's agency in tackling and countering obstacles to their political power within and beyond political institutions.